ALTERNASI SAPAAN BAHASA JAWA DI KERATON YOGYAKARTA - . Sulistyawati (Humaniora, 2008)
Javanese terms of address in the Yogyakarta palace are connected with the sociocultural aspects of the palace community. The terms of address reflect a power and solidarity in face-to-face verbal interaction either directly or indirectly. The Javanese in the Yogyakarta palace (JYP or basa bagongan) differs from the standard Javanese (SJ), especially in the first personal pronoun ‘I’. In JYP the speakers use manira, while in SJ the speakers use kula. Besides, there is a difference in the second personal pronoun ‘you’, that is, in JYP they use pakenira, while in SJ they use sampeyan or panjenengan. This study of the JYP terms of address also suggests at least three linguistic rules, i.e. alternation rules, co-occurence rules, and collocation rules. Alternation rules deal with the selection of terms of address which matches age, sex, marrital status, formality, kinship relation, and intimacy.